Pengaruh Koherensi dan Fungsi Keluarga pada Kualitas Hidup saat Pandemi COVID-19 - Azza, Irine Irchamillah; Asiyah, Siti Nur; Wardhani, Puspa (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Everyone, especially frontline workers, feels the impact of COVID-19. In dealing with COVID-19, the family has a role that can impact the quality of life of health workers and non-health workers during the COVID-19 pandemic; a good role for the family will result in better health services and increased work engagement. Research on workers in the non-health sector in pandemic conditions is still rare, making researchers choose to take two groups of subjects. It is hypothesized that there is an influence between family coherence and family functioning on the quality of life of the subjects, and there are differences between the two groups of subjects. This study's results indicate an influence between the family sense of coherence and family functioning on the quality of life of health workers and non-health workers during the COVID-19 pandemic (F= 38,978; p>0,05; adjusted R2=0,276). There is no difference in the level of quality of life between health workers and non-health workers (p=0,307; mean differences = 1,63; 95%CI[-1,52; 4,77]), but there were differences in other variables. The implication of this research is the need to strengthen the family base so it can become a source of coping for family members.